Molecular cloning and functional characterisation of NLRX1 in grass carp (Ctenopharyngodon idella). Issue 81 (October 2018) - Chu, Pengfei; He, Libo; Li, Yangyang; Huang, Rong; Liao, Lanjie; Li, Yongming; Zhu, Zuoyan; Wang, Yaping
Abstract: The nucleotide-binding domain and leucine-rich-repeat-containing (NLR) proteins regulate innate immunity. Although the positive regulatory impact of NLRs is clear, their inhibitory roles are not well defined. In the present study, the NLR family gene NLRX1 from grass carp ( Ctenopharyngodon idella ) was cloned and characterised. NLRX1 was widely expressed in all tissues examined, albeit at varying levels. After exposure to the grass carp reovirus (GCRV), NLRX1 mRNA expression levels were altered in immune organs, and dramatically altered in liver. Subcellular localisation indicated that NLRX1 protein co-localised with the mitochondria in the transfected cells. Additionally, the bimolecular fluorescence complementation (BiFC) system was introduced to detect the interaction between tumour necrosis factor (TNF) receptor associated factor 6 (TRAF6) and NLRX1. Moreover, deficient of NLRX1 in CIK cells with small interference RNA (siRNA) promoted polyinosinic:polycytidylic acid (poly (I:C))-induced IFN -related genes production, including IRF3, IRF7, and IFN-I, which reveals that NLRX1 is a negative regulator of IFN. Taken together, our results demonstrate that NLRX1 gene plays an important role in innate immune regulation and provide new insights into understanding the functional characteristics of the NLRX1 in teleosts. Highlights: The NLRX1 gene from Ctenopharyngodon idella was cloned and analysed. Expression and transcriptional regulation of the NLRX1 gene were investigated. The NLRX1 protein is localised in mitochondria and interacts with TRAF6. Poly (I:C)-induced IFN -related genes are heightened by NLRX1 silencing.